Modeling Fire Hazards Induced by Volcanic Eruptions: The Case of Stromboli (Italy) - Roberto Guardo; Giuseppe Bilotta; Gaetana Ganci; Francesco Zuccarello; Daniele Andronico; Annalisa Cappello (Fire, 2024)
We hereby present VolcFire, a new cellular automaton model for fire propagation aimed at the creation of fire hazard maps for fires of volcanic origin. The new model relies on satellite-derived input data for the topography, land-use, fuel, and humidity information, and produces probabilistic maps of fire propagation simulating fire spread. The model contains several simplifications compared to the current state-of-the-art, limiting its usability to plan fire-fighting interventions during an event in favour of a reduced computational load. The accuracy and reliability of the model are also discussed by presenting its ability to reproduce two recent fires on Stromboli island, with good spatial fit (Brier score of <semantics>0.146±0.002</semantics> for the 3 July 2019 volcanic fire, and of <semantics>0.073±0.001</semantics> for the 25 May 2022 anthropogenic fire) and less than <semantics>1.5%</semantics> variation across multiple simulations for the same event.